Agricultural practice and its relation to poverty and food security in selected river basins in Bangladesh: a situation analysis - Ghosh, Shyamal C; Rahman, ANM Mahfuzur; Raza, Wameq A (BRAC, 2019)
Poverty and food security in the context of Bangladesh has become a major concern over time. While efforts have been intensified to increase crop yield through increased land use, using inorganic fertilizers, pesticides, irrigation equipments, and so forth, these activities are frequently threatened by natural and biological hazards such as floods, cyclones, tornadoes, drought, and insects/pests. Moreover, it is assumed that the climate change induced changes of precipitation pattern would have an impact on the flooding characteristics across the basins of the Ganges, Meghna and the Brahmaputra (GMB) rivers, which might influence the agricultural land use and livelihood of people living near the river basin. This study attempts to present a situation analysis in the context of agricultural practices in the GMB basins and its relation to poverty and food security. The study finds that the riverbank areas are encumbered with a greater burden of poverty compared to the comparison areas. In terms of food security, despite the fact that one third of the households reported being chronically poor, more than 95% households in 2008 reported to be food secured. Hence, the households in comparison areas were found in a relatively better situation compared to the riverbank areas.